Islam and Culture: Harmony of Differences in a Diverse Society - Ernawaty Mappigau; Bahaking Rama; M. Ilham Muchtar (Diplomasi : Jurnal Demokrasi, Pemerintahan dan Pemberdayaan Masyarakat, 2026)
This study analyzes the relationship between Islam and culture through three main focuses. First, the research explores the role of culture in shaping the religious practices and social ethics of Muslims. Culture acts as a medium that influences how individuals understand religious teachings and perform worship. Second, the study examines the dialogue between basic Islamic values ​​and local culture through the process of acculturation. The analysis shows that the interaction between the two results in patterns of acceptance, adaptation, or correction of local customs. Challenges often arise when cultural values ​​conflict with principles of faith and morality. Third, the research assesses Islam's ability to adapt in a global context and its contribution to humanity and modern civilization. Islam promotes an ethic of justice, moderation, and social responsibility that is relevant to global issues. This study illustrates that Islam is dynamic and capable of dialogue with various cultures as long as it does not conflict with the basic principles of sharia.